Keupayaan Konkrit Campuran Polimer Polipropilena Termoplastik (PPT) Sebagai Bahan Tambah - Mohd Noorfiza, Nur Farra Farysha; Othman, Nor Hazurina (Recent Trends in Civil Engineering and Built Environment, 2024)
Thermoplastic polymers polypropylene, which are utilized as an addition in concrete, are used to make beverage dispensers. This study was conducted to study the compressive strength of thermoplastic polymer polypropylene (PPT) mixed concrete. The objective of this study was to determine the optimum percentage value of thermoplastic polymer polypropylene (PPT) in concrete. In addition, study the compressive strength of concrete thermoplastic polymer polypropylene (PPT) mixtures. This study was carried out with a concrete mix of  used that is 0% (control sample), 0.5%, 1% and 1.5%. A total of 48 concrete samples were produced in cubes measuring 100mm x 100mm x 100mm. The tests that have been carried out are sieve analysis test, specific gravity test, slump test, curing, density test and compression test. As the result, it was found that the optimal percentage of polypropylene polymer thermoplastic (PPT) mixture was 0.5% (KPPT0.5).